The Implementation of Burhanuddin al-Zarnuji's Thoughts on the Morals of Students at the Darul Ulum Islamic Boarding School in Padang - Syafrizal, Syafrizal; Samad, Duski; Zalnur, Muhammad (Jurnal Kajian dan Pengembangan Umat, 2025)
This study aims to analyze the implementation of moral values among Islamic boarding school students based on the thoughts of Burhanuddin al-Zarnuji as described in the book Ta'lim al- Muta'allim at the Darul 'Ulum Islamic Boarding School in Padang. The type of research used is field research with a descriptive qualitative approach. Data was obtained through observation, interviews, and documentation, which were then analyzed in depth to describe the application of moral values in the lives of santri. The results of the study show that the process of moral character building at the Darul 'Ulum Islamic Boarding School has been going well and reflects the main values in Ta'lim al-Muta'allim, such as respect for teachers, politeness, discipline, and manners towards knowledge and others. The main supporting factors for this success include the exemplary behavior of the teachers, the role of senior students, and a conducive and religious boarding school environment. However, the process of moral development still faces several obstacles, such as a lack of dormitory supervisors, limited facilities and infrastructure, and the influence of outside cultures that cannot be completely avoided. This study concludes that the character building of students at the Darul 'Ulum Islamic Boarding School has shown positive results, but needs to be strengthened in terms of guidance and supervision so that moral values are not only understood conceptually, but are truly internalized in the behavior and character of the students.